Operation of a Capacitive Pumped CuBr Laser in a Reduced Energy Deposition Mode; Electron Devices and Materials (EDM), Annual Siberian Russian Workshop; Micro/Nanotechnologies and Electron Devices (EDM) - Musorov I. S. Ilia Sergeevich; Ogorodnikov D. N. Dmitry Nikolaevich; Shiyanov D. V. Dmitry Valeryevich; Sukhanov V. B. Viktor Borisovich; Torgaev S. N. Stanislav Nikolaevich; Evtushenko G. S. Gennady Sergeevich (2020, 2020)
Title screen